K-mean cluster analysis of the use of prepositional phrases for location, writing, reading, and understanding words presented in a three-dimensional, puzzled, and distorted form - Salkić, Naim; Povlakić Hadžiefendić, Meliha (Technium Social Sciences Journal, 2024)
The primary objective of this study is to examine the statistically homogeneous clustering in the hierarchical arrangement of the use of adverbial clauses for location, recognition, and comprehension of words presented in three-dimensional, rebus, and distorted forms. The study was conducted on a sample of 140 participants. The first subset of participants constituted the experimental group, consisting of 70 deaf students, while the second subset formed the control group, comprising 70 hearing students of the same chronological age. A battery of tests was utilized as a measurement instrument, including the “Test of Writing and Comprehending Adverbial Clauses for Location,” “Test of Reading, Writing, and Comprehending Words Presented in Three-Dimensional Form,” “Test of Reading, Writing, and Comprehending Words Presented in Rebus Form,” and “Test of Reading, Writing, and Comprehending Words Presented in Distorted Form.” In the descriptive analysis, frequencies of the total words achieved by both deaf and hearing participants were computed for the different types of measurement instruments employed. To identify the most robust homogeneity of participants concerning the applied variables, non-hierarchical and hierarchical Cluster Analyses were employed. The research results indicate a significant lag in the use of adverbial clauses for location, writing, reading, and understanding words presented in three-dimensional, rebus, and distorted forms among deaf children in comparison to their hearing peers. The Cluster Analysis revealed the most significant linkage between the variable “Number of used adverbial clauses for location” and the variable “Number of recognized words presented in three-dimensional form.” This link was clustered with the variable “Number of written words presented in rebus form” and the variable “Number of written words presented in three-dimensional form.” An analysis of variance for isolated clusters identified a statistically significant difference in the entire measurement space of adverbial clauses for location, three-dimensional, rebus, and distorted forms of words, with a level of statistical significance at p=0.00.